Effect of the Glycemic Index of Selected Types of Dates on Metabolic Response and Physical Performance in Trained Athletes - Mohammed Hasan Tuaimah (Tadulako Journal Sport Sciences And Physical Education, 2026)
This study used a randomized controlled trial with thirty (30) volleyball athletes. They were given a fixed amount of carbohydrates (50-70g) before physical activity, in accordance with existing guidelines for pre-exercise nutritional supplementation. Various measures were evaluated. Metabolic indicators included blood glucose concentration, insulin concentration, and lactate concentration. Physical fitness was also assessed through endurance tests. Significant differences were found between the three groups in blood glucose, insulin, lactate, and physical performance (p ≤ 0.05). Zahidi dates produced the most stable metabolic response, indicated by the lowest mean blood glucose (90 ± 5 mg/dL) and insulin levels (9.2 ± 1.1 μIU/mL) compared to Qaranfali and Medjool. Conversely, Qaranfali showed the highest physical performance results (1300 m) and the highest rate of improvement (16.0%), followed by Medjool (1280 m; 15.3%) and Zahidi (1250 m; 13.6%). These results suggest that dates with a low glycemic index support metabolic stability, while those with a moderate glycemic index may be more beneficial for sports performance. Furthermore, the choice of date type should be tailored to the nature and timing of physical activity, as it is recommended to use dates with a low glycemic index before prolonged exercise to improve metabolic stability, while dates with a high glycemic index can be used for short-term activities or during periods of rapid recovery. The study concludes that dates are an effective and reliable natural food source for sports nutrition strategies. This opens the door to further applied research in various sports settings, especially in date-producing countries.